An assessment of functional outcome and management of metacarpal and phalangeal fractures of hand with universal mini external fixator - Vijayanand, Addanki; Penchalaih, Alam (International Journal of Research in Orthopaedics, 2020)
Background: Trauma to the hand is quite common and may result in fractures of the bones. Hand fractures can be complicated by deformity from no treatment, stiffness from over treatment and both deformity and stiffness from poor treatment. To evaluate the outcome of metacarpal and phalangeal fractures managed with UMEX (universal mini external fixator) in order to assess their usefulness in different fracture types and to make recommendations regarding potential applications. Methods: A one-year prospective study at Narayana medical college was conducted and 50 cases were included following the inclusion criteria. All the cases were evaluated and assessment of injury was done by Swnason’s criteria. UMEX application was done on all cases and follow up was done and functional assessment done following Duncan’s criteria. Results: Male predominance was observed, 21-40 years was common age group (30%) and RTA was common cause (72%). 57 total fractures with 66.7% in right hand, 45.62% were metacarpals, 36.84% proximal phalanx and 80% were shaft fractures. 61.4% of cases had radiological union within 8-12 weeks and partial stiffness was the commonest complication (52.17%). As per the Duncan’s criteria, 44% had good outcome, 40% had excellent outcome, 10% had fair and 6% had poor outcome. Conclusions: UMEX is an adequate treatment modality for multiple, intra articular and open fractures. Understanding the basic principles and correct application methodology is absolutely essential for optimal usage of the equipment. It’s a useful tool in management of small fractures of the hand.